The effect of aluminum oxide sandblasting on immediate dentin sealing - Belbut, M. (2018)
Poster presented at the CED-IADR/NOF Oral Health Research Congress (2017 Continental European and Scandinavian Divisions Meeting). September 21-23 2017, Vienna, Austria